An analysis of Loan Loss Provisioning behavior and Cost Efficiency in Chinese Commercial Banks - JIN, XIAOYU (2018)
This study employs a panel dataset of 200 Chinese commercial banks during 2011-2017, aiming to examine the loan loss provision behaviour in the Chinese banking industry. Considering X-efficiency is one of the important factors to measure bank performance, this study includes X-efficiency as one of the independent variables to test the relationship between Chinese banks’ efficiency scores and LLP behaviours. Hence, the estimated efficiency scores which measured by the Stochastic Frontier Analysis (SFA) method will be incorporated into the regression of LLP as an independent variable. Moreover, the two-step System Generalized Methods of Moments (GMM) will be used to analyse three hypotheses, X-efficiency and other explanatory variables. It is found that the average efficiency of Chinese banks is 89.07% and there is a relatively stable efficiency level over the specific period. In the LLP regression, we found evidence for the existence of procyclicality and income smoothing behaviour, but there is no evidence to support the capital management hypothesis. Furthermore, this study finds a negative but insignificant relationship between LLP and bank efficiency scores.